KEWENANGAN MENGADILI BADAN DAN/ATAU PEJABAT PEMERINTAH (ONRECHTMATIGE OVERHEIDSDAAD) YANG BERSIFAT KEPERDATAAN - Wibawa Sitanggang, Riko (Honeste Vivere, 2025)
In practice, there is indeed a limitation of competence between the State Administrative Court and the General Court within the scope of the Supreme Court of Indonesia (Peraturan Mahkamah Agung Republik Indonesia No. 2 Tahun 2019 dan Surat Edaran Mahkamah Agung Republik Indonesia No. 2 Tahun 2019). However, the principle of justice prioritises the idea that courts cannot reject submitted applications (ius curia novit), particularly for those seeking justice. The development of judicial competence certainly brings about legal events that require judges to examine cases submitted to them based on applicable law (rechtmatigheid) and legislation (wetmatigheid), regardless of whether the case falls into the category of absolute inter-judicial competence. This is particularly important when legal events involve government agencies and/or officials, while ensuring that the applicant's sense of justice as a justice seeker is not harmed or eliminated.